Pengaruh Kompetensi Pegawai dan Iklim Organisasi Terhadap Kualitas Pelayanan di Unit Pelaksana Pelayanan Terpadu Satu Pintu Kota Administrasi Jakarta Barat - A.H. Rahadian; Albertina Novi; Sri Sundari; Mary Ismowati (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2018)
This study aims to determine how much Effect of Employee Competence and Organizational Climate on the Quality of Customer Service in One Stop Integrated Service Unit West Jakarta Administration, by taking a sample of 93 respondents. Both independent variables and the dependent variable is operationalized by research method as follows: Sampling is done by using the technique sampling; Scoring of answers of respondents using a Likert Scale Technique; using Quantitative Descriptive Data Analysis. From the above results, it can be concluded that the hypothesis that the authors propose is acceptable, because there is a positive Effect of Employee Competence and Organizational Climate either partially or simultaneously on the Quality of Customer Service in One Stop Integrated Service Unit West Jakarta Administration.